Animalar: an interactive tool in learning educational animal kingdom through augmented reality / Muhammad Afif Danial Muhammad Honorius, Norzatul Bazamah Azman Shah and Muhammad Hamiz Mohd Radzi - Muhammad Honorius, Muhammad Afif Danial; Azman Shah, Norzatul Bazamah; Mohd Radzi, Muhammad Hamiz (College of Computing, Informatics, and Mathematics, 2024)
The education of the animal kingdom is the domain of this work. The project's main goal is to solve the issue that younger people, particularly those in primary school, have when learning about animals. The issue is that people do not know enough about the animal realm, and learning about animals is uninteresting. The objectives of this project are to design a 3D environment with variety of animals in it, to develop a mobile application that uses augmented reality in learning animal and to evaluate the usability of the mobile application. The methodology that being used for this project is Agile methodology and the technique being used for augmented reality application is the marker-less technique. Testing was conducted at the Sekolah Kebangsaan Senai Utama to validate the project's functionality and usability through the students and the science teachers. The results of the testing phase revealed it successfully achieve the objectives. In conclusion, this project contributes significantly to the students and the science teachers, providing valuable insights into one of the latest technologies that can be utilize in educational aspect. Moving forward, potential future work that include augmented reality application or other technology that related to it will be improve to ensure it will satisfy and contribute more to the public.